The Effect of IFRS Convergence toward Earnings Management with Managerial Ownership as a Moderating Variable - Wahyuningrum, Indah Fajarini Sri; Rizqi, Dessy Munfa’ati (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
This study aims to determine the effect of IFRS convergence on earnings management using corporate governance as a moderating variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period of 2015-2017. This study used a purposive sampling method to select 38 companies with 114 units of analysis. The results indicate that IFRS convergence do not affect earnings management. The results also show that managerial ownership and auditor quality cannot moderate the influence of IFRS on earnings management. Meanwhile, the number of audit committee meetings can alter the effect of IFRS convergence on earnings management.